Making the connections: Autophagy and post-translational modifications in cardiomyocytes. Issue 11 (1st November 2016) - Gupta, Manish K.; Robbins, Jeffrey
ABSTRACT: Cardiac proteins are subject to continuous stress and these intrinsic and extrinsic factors, both physiological and pathological can lead to protein misfolding. If the protein quality control (PQC) pathways are in any way compromised or their activities diminished, intracellular aggregates can form and a proteotoxic environment is generated, which contributes to cardiac disease and heart failure. We studied the role that SUMO post-translational modification plays in a proteotoxic cardiac environment. SUMOylation can have an integral role in controlling flux through the ubiquitin-proteasome system, and expression of the SUMO (small ubiquitin-like modifier) E2 enzyme UBE2I/UBC9 improves cardiac PQC. Our data focus on using gain- and loss-of-function approaches to modify UBE2I levels and measure the effects on cardiomyocyte autophagic flux. UBE2I expression does have an impact on macroautophagy/autophagy as increased SUMOylation results in increased autophagy. We show that increased SUMOylation is cardioprotective and can decrease morbidity in proteotoxic cardiac disease.